The right to choose: An ethical and legal dialogue on abortion andassisted suicide - Rodríguez Contreras, Juan Carlos (Revista Internacional & Comparada de Derechos Humanos, 2026)
This text begins with a philosophical and legal discussion of two deeply controversial topics: abortion and assisted suicide. Taking as its starting point the reflections contained in Ronald Dworkin’s Justice for Hedgehogs (2011), this text also explores the contributions of contemporary thinkers such as Michael Sandel (2009), John Rawls (1995), Robert George (1999), Juan Miguel Zunzunegui (2012), and classics such as Socrates, Plato, Aristotle, and Augustine of Hippo. The aim is not to issue a definitive judgment, but rather to present a comprehensive and rigorous analysis of the main ethical and legal foundations at stake, while also incorporating a faithful reconstruction of a critical conversation between the author and a reflective interlocutor.